MODELING AND OPTIMIZATION OF HUMAN RESOURCES (POP-SDM) IN IMPROVING TEACHER INNOVATIVENESS IN TASIKMALAYA REGENCY - Kencanawaty, Gita; Hardhienata, Soewarto; Herfina, Herfina (Yayasan Education and Social Center, 2025)
The purpose of this study was to test a model for increasing teacher innovation through strengthening the variables of work motivation, knowledge sharing, organizational culture, and creativity. The method used in this study was a mixed method with a POP-SDM approach. The sample in this study consisted of 163 teachers taken from 43 public elementary schools in Tasikmalaya Regency. The results of the study show that R² = 0.820, meaning that 82% of the exogenous variables jointly influence the endogenous variables. Teacher innovation (Q² = 0.508). A Q² value of 0.508 indicates that the model has strong predictive power for the teacher innovation variable. BIC (Bayesian Information Criterion) -115.125 is the lowest value in the initial model, thus the initial model chosen in this study is the best model.